Phenospectral similarity as an index of ecological integrity - Osei Darko, Patrick; Laliberté, Etienne; Kalacska, Margaret; Arroyo‐Mora, J. Pablo; Gonzalez, Andrew; Zuloaga, Juan (Frontiers in Environmental Science, 2024)
In collaboration with the International Union for the Conservation of Nature (IUCN) Taskforce on Biodiversity and Protected Areas, countries worldwide are working to develop a new systematic approach to inform the Key Biodiversity Areas (KBA) initiative. The goal is to map KBAs from national to global scales with a baseline international standard in support of biodiversity conservation efforts. According to the IUCN standard, one of the five criteria used to identify Potential KBAs is the Ecological Integrity (EI) of the ecosystem. Sites identified with respect to EI must have an intact ecological community and be characterized by minimal anthropogenic disturbance. In this study a new EI metric, phenospectral similarity (PSpecM), has been developed and implemented in Google Earth Engine to identify potential forest stands of high EI from a large set of candidate stands. The implementation of the PSpecM requires a network of known reference sites of high EI and target ecological units of the same land cover type for comparison to help identify potential sites of high EI. Here we tested the PSpecM on ~12,000 km2 study area in Laurentian region, Quebec, Canada using Sentinel-2 and PlanetScope (Dove) satellite imagery. Considering the phenological effect on reflectance, we found a 2700 km² spatial extent, equivalent to approximately 22% of the study area, commonly delineated as potential areas of high EI by both Planetscope (Dove) and Sentinel-2. Without consideration of phenology the total area delineated as potential areas of high EI increased to 5505 km², equivalent to around 45% of the study area. Our results show that the PSpecM can be computed for rapid assessments of forest stands to identify potential areas of high EI on a large geographic scale and serve as an additional conservation tool that can be applied to the ongoing global and national identification of KBAs.